PERANCANGAN BRAND UNTUK STUDIO PENGEMBANG APLIKASI KREATIF - Tri Wahyu Oktalia Agung Wiyono; Christian Anggrianto (Universitas Ciputra Surabaya, 2016)
The growth of smartphone users in Indonesia continues to increase, Indonesia can be considered as a promising market for smartphone application industry. But not many local businesses taking serious effort into this market. Local applications available at this market also tend to be deficient and can not compete with foreign applications, it also create a negative perception in the community to the Indonesian application developer. The research method is done by observations, and interviewing extreme and expert user, brings out a conclusion that it requires a high quality local application development studio brand to solve.